Training and hiring strategies to improve firm performance - Mika Maliranta; Rita Asplund (The Research Institute of the Finnish Economy (ETLA), 2007)
We study how upgrading the skills of the personnel affects a firm's performance. Two different strategies are examined: 1) providing formal training and 2) strategic recruitment and separation policy. The use of register-based longitudinal employeremployee data supplemented with a survey on vocational training provides an opportunity to shed fresh light on the issue and allows us to address the usual econometric problems. We find that internally (but not externally) organized training stimulates subsequent growth of performance but only when combined with the implementation of new process or product technology. Hiring highly skilled workers is initially costly to firms but is productivityenhancing in the long run.
Keywords: J24; M5; O3; D2; 330; Productivity; profitability; training; education; hiring; Produktivität; Humankapital; Bildungsniveau; Berufsbegleitende Ausbildung; Personalbeschaffung; Personalauswahl; Schätzung; Finnland